Biochemical composition and quality dining sorts of potatoes grown in the light-brown soils Astrakhan region drip irrigation - A F Tumanyan; N V Tutuma; N A Shcherbakova (RUDN Journal of Agronomy and Animal Industries, 2016)
Potatoes - one of the most important human food. It has high taste and nutritional properties. The optimum ratio in potato tubers of organic and mineral substances essential to man, determines its value as food. The tuber contains on average 76-78% of water and from 13 to 36% solids, of which 12-15% is starch, 1-3% protein and about 1% - mineral compounds. Proteins potatoes have a very high biological value because they contain a set of essential amino acids that are not synthesized in the human body and must be obtained from food. The potato is the most important source of vitamin C. Potato protein is extremely biological value through the optimal ratio of essential amino acids, surpassing peas and beans on the content of methionine and grains - on the content of lysine. The aim of research was to evaluate cultivated on light-brown soils under drip irrigation of potato varieties biochemical indicators and dining. As a result of under drip irrigation on light-brown soils of the Astrakhan region studying the collection of early and Medium early varieties for a number of biochemical parameters were identified early varieties - Dolphin Karatop, good luck, and is mid - Innovator, Resource, The blue, effect, Nevsky, cover, Zhukov Jubilee. Indicators on the table were the best varieties Dolphin Resource The blue, Nevsky Innovator.